The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1111/j.1365-2605.1990.tb00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic localization of [3H]oestradiol in epididymis, seminal vesicles and prostate of the fetal guinea‐pig

Abstract: The selective uptake and localization of radioactivity in the fetal male reproductive organs (epididymis, seminal vesicles and prostate) of the guinea-pig (50-60 days of gestation) after in-vivo and in-situ subcutaneous injection of [3H]oestradiol was investigated by autoradiography. In 50-day-old fetuses, the different areas of the epididymis showed selective retention of radioactivity in the nuclei of peritubular and stromal cells surrounding the epididymal duct; no retention was observed in the epididymal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Thus, ERa and ERb are present in both stromal and epithelial tissues of the prostate during various developmental and adult stages. However, it is notable that steroid autoradiographic studies in various species and different developmental stages have consistently demonstrated the binding of 3 H-estradiol in the prostatic stroma but not in the epithelium (Cooke et al, 1991b;Hatier et al, 1990;Weaker and Sheridan, 1982). As described above, the induction of squamous metaplasia in prostatic epithelium is dependent upon ERa (and not ERb), and ERa is required simultaneously in both the epithelium and the stroma (Risbridger et al, 2001b).…”
Section: Hormonal Carcinogenesis In the Prostate Is Independent Of Epmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, ERa and ERb are present in both stromal and epithelial tissues of the prostate during various developmental and adult stages. However, it is notable that steroid autoradiographic studies in various species and different developmental stages have consistently demonstrated the binding of 3 H-estradiol in the prostatic stroma but not in the epithelium (Cooke et al, 1991b;Hatier et al, 1990;Weaker and Sheridan, 1982). As described above, the induction of squamous metaplasia in prostatic epithelium is dependent upon ERa (and not ERb), and ERa is required simultaneously in both the epithelium and the stroma (Risbridger et al, 2001b).…”
Section: Hormonal Carcinogenesis In the Prostate Is Independent Of Epmentioning
confidence: 88%
“…Estrogens act through two specific receptors, ERa and ERb (Couse and Korach, 1999;Kuiper et al, 1996). However, it is notable that steroid autoradiographic studies in various species and different developmental stages have consistently demonstrated the binding of 3 H-estradiol in the prostatic stroma but not in the epithelium (Cooke et al, 1991b;Hatier et al, 1990;Weaker and Sheridan, 1982). ERb, which was originally cloned from prostatic tissue, is expressed at high levels in both prostatic epithelium and stroma in the developing prostate.…”
Section: Hormonal Carcinogenesis In the Prostate Is Independent Of Epmentioning
confidence: 99%
“…In this regard, in recent autoradiographic studies we found that in the fetal rat uterus, radioactive estra¬ diol was located mainly in the stromal cells (24). Ennis & Stumpf (25) demonstrated that estradiol and 4-hydroxytamoxifen can differentially affect progestin binding sites among the uterine tissue compartments of the immature rat, but for these two compounds the main interactive region is in the stroma.…”
Section: Discussionmentioning
confidence: 95%